What transformation? A qualitative study of empowering settings and community mental health organizations - Monteiro, Maria Fátima Jorge (2015)
This article is based on empowering settings research and has a two-fold objective: to propose an adaptation of the empowering community settings framework to community mental health organizations practice to foster recovery and community integration; and to discuss how the adapted framework is a relevant tool to challenge community mental health transformation at multiple levels of analysis. The current study was anchored in a larger qualitative research project. It used a case study approach, with 8 in-depth interviews with diverse participants from one community mental health organization. The adapted model proved useful to guide transformational practice in community mental health programs and for evaluation of organizational empowerment and multilevel community-oriented interventions. Suggestions and implications for future research are also presented.